Mathematical simulation of motion of working medium at finishing-grinding treatment in the oscillating reservoir - Mamalis, A. G.; Grabchenko, A. I.; Mitsyk, A. V.; Fedorovich, V. A.; Kundrak, J. (Springer-Verlag London, 2014)
The results of mathematical simulation have been carried out for the pattern of working medium motion providing the technological process of finishing–grinding treatment in an oscillating reservoir. With use of physics laws, it is ascertained and grounded that the flow of granules at the plane wall of reservoir is travelling oppositely to the source of vibrations, whereas the granules are drifting on the cycloid–trochoid trajectories from the wall of reservoir, where the looped displacement is maximal, to the center of reservoir in which the shift of granules is reduced to minimum because of damping and dissipation effect. The received theoretical regulations have a fundamental nature and can be used at the account of technological parameters of designed vibration machines.
Keywords: grinding; vibrations; mathematical simulation